2008
DOI: 10.1021/jp711028w
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Self-Regulated Cluster Growth on the TiO2(110) Surface Studied Using Polarization-Dependent Total Reflection Fluorescence XAFS

Abstract: Three-dimensional structures of Ni clusters deposited on a TiO2(110) surface were studied using polarization-dependent total reflection fluorescence X-ray absorption fine structure (PTRF-XAFS) analysis. Three-dimensional Ni clusters were formed with a slightly anisotropic structure at 1 × 1014 atoms/cm2. The PTRF-XAFS results for a 1 × 1014 atoms/cm2 sample revealed the formation of one-atomic-layer Ni clusters with a distorted (110)fcc plane structure. We found a Ni−Ni distance of 0.240 nm with Ni−O interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 79 publications
(145 reference statements)
0
19
0
Order By: Relevance
“…Single-layer Ni clusters are stabilized by multiple bonds to surface oxygen atoms. 9 Single-layer Ni was seen to deform to an fcc (110)-like structure to increase contact with the surface oxygen atoms. About 90% of the Ni atoms had averaged Ni-O bond distances of 2.3 ± 0.1 Å.…”
mentioning
confidence: 99%
“…Single-layer Ni clusters are stabilized by multiple bonds to surface oxygen atoms. 9 Single-layer Ni was seen to deform to an fcc (110)-like structure to increase contact with the surface oxygen atoms. About 90% of the Ni atoms had averaged Ni-O bond distances of 2.3 ± 0.1 Å.…”
mentioning
confidence: 99%
“…Considering the anisotropic surface structure of TiO 2 (110), XAFS were carried out in three different orientations relative to the electric vector (E) of the incident X-rays. [9][10][11] Data analysis was processed using REX 2000 software (Rigaku) and FEFF code. 16 XRD data were recorded on an Ultiama IV diffractometer (CuKA, 40 kV, 40 mA; scan speed: 2 degree/min; step: 0.1 degree, Rigaku).…”
Section: Methodsmentioning
confidence: 99%
“…Especially, it has been demonstrated that polarization-dependent total reflection fluorescence XAFS (PTRF-XAFS) technique is a powerful tool for obtaining 3D structure on a flat substrate. [9][10][11] In this study we have examined the structure of HKUST-1 12 ([Cu 3 (BTC) 2 (H 2 O) 3 ] n ; BTC = 1,3,5-benzenetricaboxylate) thin films on a single crystal rutile Nb-doped TiO 2 (110) surface in which properties can be enhanced than non-doped TiO 2 (110) for understanding the growth mechanism of MOFs film. HKUST-1 is one of well-known functional MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…The Ni atoms can find other Ni to form clusters before reaching the step edges if the surface density of Ni is high. 27,29) At less than the critical coverage, Ni atoms can reach the step edge site without colliding with other Ni atoms. Here, two Ni-O bonds can fix the Ni atoms.…”
Section: Ni On Tio 2 (110)mentioning
confidence: 99%